The spectrum of beta-globin gene mutations in children with beta-thalassaemia major from Kota Kinabalu, Sabah, Malaysia - Thong, M.K.; Soo, T.L. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2005)
This finding confirmed the deletion in the homozygous state was associated with a severe phenotype. The reason for the predominance of this mutation in Kota Kinabalu is most likely to be due to founder effects and possibly intermarriages between the various ethnic groups. Prenatal diagnosis using PCR for this common mutation is feasible in this community. Medical workers and scientists at molecular diagnostic centres serving large South East Asian populations should incorporate a diagnostic strategy for this deletion in the appropriate population. Future studies on these indigenous ethnic groups in other areas and other groups in Sabah are required.